PENGARUH LATIHAN SMASH TANPA BOLA DAN LATIHAN SMASH BOLA DIAM TERHADAP KEMAMPUAN SMASH BOLAVOLI - Resa Sukardi Massa; Suprianto Kadir (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2019)
This research is a field experimental study that aims to find out the difference between the effects of non-ball smash exercises and silent ball smash exercises on the ability of volleyball smash on students of the FOK UNG Sports Coaching Education Study Program. The population and sample involved in this study were 60 students of the FOK UNG Sports Coaching Education Study Program. However, in accordance with the research design, two research groups were formed which consisted of ball-free smash exercises and silent ball smash exercises. The research was carried out for six weeks with frequency of exercise 3 times a week. Based on the results of data analysis using the paired t-test formula and the unpaired ttest at a significant level of 95%, it can be concluded as follows: There is a significant effect of smash training without the ball on the ability to do volleyball smash (to = 8,869> tt = 2,045 ). There is a significant effect of the silent ball smash exercise on the ability to do volleyball smash (to = 13,535> tt = 2,045). There is a significant difference in the effect between the smash ball practice without the ball and the silent ball smash exercise on the ability to do volleyball smash (to = 8,259> tt = 2,000)